2019
DOI: 10.1007/s42452-019-0362-2
|View full text |Cite
|
Sign up to set email alerts
|

Phytogenic synthesis of silver nanobactericides for anti-biofilm activity against human pathogen H. pylori

Abstract: The present study reports the phytogenic synthesis of silver nanobactericides using Acorus calamus L. and their antibiofilm activity against clinically isolated H. pylori. The synthesis was confirmed with change in the color of the reaction mixture to brown. The increased in the color intensity was periodically monitored with UV-visible spectroscopy which displayed maximum absorption at 410 nm. The biomolecular interaction was studied with FTIR spectral measurements of silver nanobactericides which revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The biofilm inhibitory activity was evaluated against Helicobacter pylori clinical isolates. The synthesized NPs exhibited significant antibiofilm activity at concentration 350 μg/ml, as evidenced by crystal violet and ruthenium red assays (Prasad et al, 2019).…”
Section: Silver Nanoparticlesmentioning
confidence: 95%
“…The biofilm inhibitory activity was evaluated against Helicobacter pylori clinical isolates. The synthesized NPs exhibited significant antibiofilm activity at concentration 350 μg/ml, as evidenced by crystal violet and ruthenium red assays (Prasad et al, 2019).…”
Section: Silver Nanoparticlesmentioning
confidence: 95%
“…Non-spherical silver ultrananoclusters, with the smallest size of all the AgNPs, were used in a single study [ 124 ], and they showed a high degree of growth inhibition of the bacterium when the dosage was between 0.16 and 0.33 mg/L. In the vast majority of the studies, spherical silver nanoparticles were used, obtained from different extracts, having various sizes: A. priceps , 5–30 nm [ 125 ]; S. xanthocarpum , 4–18 nm [ 32 , 126 ]; T. vernicifluum , 4–20 nm [ 127 ]; C. longa [ 128 ] and A. nilotica , 22–66 nm [ 124 ]; P. putida , 6–16 nm [ 35 ]; A. calamus , 5–60 nm [ 129 ]; A. nilotica , 22–55 nm [ 130 ]. The most common effect on the bacterial colonies was inhibition of growth, which was presented in six of the papers [ 124 , 125 , 127 , 128 , 131 , 132 , 133 , 134 ], followed by activation of reactive oxygen species production [ 130 , 132 ], inactivation of H. pylori urease [ 131 , 135 ], bacterial DNA fragmentation and consecutive loss of viability [ 130 ], damage to the bacterial cellular membrane [ 132 ], and activation of antioxidant activity [ 136 ].…”
Section: The Antibacterial Mechanism Of Silver Nanoparticles: An Exte...mentioning
confidence: 99%